Mechanistic role of FN1 in LAIR-1 mediated downregulation of ovarian cancer cell proliferation - Huachang Zhang; Mengke Liu; Hao Zhong; Li Ma; Yunyi Liu; Chuntong Liu; Shude Yang; Bin Wang; Jing An; Shuling Song; Qizhi Cao (BMC Cancer)
Abstract Objective RNA-seq was used to explore the potential mechanism underlying human leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1) inhibition of the proliferation and migration of ovarian cancer cells. Method A LAIR-1–overexpression cell model was established using a LAIR-1-lentivirus. After confirming and identifying the LAIR-1 expression cell clones by flow cytometry and RT-qPCR, the proliferation and migration of the cells were examined by CCK8 and scratch assays, and the differentially expressed genes (DEGs) were searched by RNA-seq and analyzed by GO and KEGG enrichment. String was used for protein interaction network analysis, and Cytoscape was used to identify key proteins. Results LAIR-1 inhibited the proliferation and migration of ovarian cancer cells. LAIR-1 expression caused the upregulation of 83 genes and the downregulation of 80 genes. Among the DEGs, fibronectin 1 (FN1) was a key protein affecting the downstream FAK-MEK-ERK axis. KEGG enrichment analysis identified the MAPK pathway as the most obvious enrichment pathway, followed by PI3K-AKT pathway. Conclusion LAIR-1 downregulates FN1 to inhibit the FAK-MEK-ERK axis, as well as the proliferation and migration of ovarian cancer cells.